An Investigation of Asset Write-Downs and Concurrent Abnormal Accruals - Rees, Lynn; Gill, Susan; Gore, Richard (Journal of Accounting Research, 1996)
Lynn Rees, Susan Gill, Richard Gore, An Investigation of Asset Write-Downs and Concurrent Abnormal Accruals, Journal of Accounting Research, Vol. 34, Studies on Recognition, Measurement, and Disclosure Issues in Accounting (1996), pp. 157-169